Penggunaan Bahasa Slang Remaja Dari Masa Ke Masa Di Batam - Suhardianto Suhardianto; Melly Siska Suryani (Prosiding, 2018)
This study aims to find the construction and perspective of the use of Indonesian language slang in Batam from time to time from the 1980s to the 2000s. Data collection methods are observation and interview methods. The technique used is "Bebas Libat Cakap and Pancing" (Sudaryanto, 2015). In the process of analyzing the data, the researcher uses the method of Padan and Agih. The method is used to see the construction of slang in each period while the matching method is used to describe the teenage’s perspective in the use of slang from time to time. The results showed that there were differences in the shape and context of using slang in the 80s and 2000s. The way in which non-standard languages differ from one another. The 2000s slang language, for example, is formed by changing "a" to "e" in the last syllable and the First Syllable Abolition. The transformational language that is the 80s era slang form is formed by Ga, Gi, Gu, Ge, Go formulas after single syllable vowels, Ga / G, Gi, Gu, Ge, Go formulas before repeated syllables, formula Ga, Gi, Gu, Ge, Go before the last consonant, and the Ga, Gi, Gu, Ge, Go formulas for cluster consonants. The perspective of using slang language can be found the highest percentage of 30.76% slang language used because others want to be cool, 46.42% colloquial language is used with the aim of easy to communicate, and 66.66% of transformational languages are used because they want to hide something from others.